Physics design of a coupled RFQ-DTL cavity for a compact neutron source. (25th August 2021) - Tan, Q.Y.; Lu, Y.R.; Wang, Z.; Zhu, K.; Liu, S.; Han, M.Y.
Abstract: Neutrons have been widely used, such as neutron imaging, transmutation of nuclear waste, Neutron Capture Therapy (NCT), et al. Neutrons are generally produced by nuclear reactors or accelerator-driven neutron sources. Comparing with nuclear reactors, accelerator-driven neutron sources have many advantages, such as compact and cheap. We proposed a coupled RFQ-DTL cavity as the main component of a miniaturized neutron source. A high accelerating efficiency was achieved by placing Radio Frequency Quadrupole (RFQ) and Drift Tube Linac (DTL) in one cavity. Since the fringe field will increase the energy spread, we propose a method using the fringe field as a buncher to reduce the negative effect, and it will eliminate the use of external bunchers. The coupled RFQ-DTL cavity will accelerator a 25 mA proton beam from 35 keV to 2.5 MeV within 2.23 m. RFQ section and DTL section are 1.55 m and 0.68 m, respectively. Compared with a conventional RFQ, the length of coupled RFQ-DTL is shorten by 53%. The total transmission efficiency is 98.55%. A variable energy design for the beam output energy can be achieved by changing the insertion depth of the DTL tuner and controlling the feeding power of the cavity.